Adequate plant densities to increase agricultural rice yield - Calero Hurtado, Alexander [UNESP]; Perez Diaz, Yanery; Quintero Rodriguez, Elieni; Gonzalez-Pardo Hurtado, Yainier (Univ Central Marta Abreu Las Villas, 2021)
The use of adequate plant densities can be a key and important factor to increasing rice productivity (Oryza sativa L.). Therefore, the objective of this study was to investigate the influence of four population densities (DP) on the growth and agricultural production of rice. The INCA-LP-5 cultivar was managed between April and August 2016. The treatments were distributed in a randomized block design, with four population densities (250,000, 350,000, 450,000 and 550,000 plants ha(-1)) and five replications. The effects of the PD were verified by observing the following parameters: evaluated the following indicators, plant height (cm), tiller number per hill, number of panicles per m(2), number of grains per panicle, panicle length (cm), 1000 grains weight (g) and grain yield (t ha(-1)). The results indicated that the DP of 450,000 plant ha(-1) showed the best results in rice productivity. These results were possible because the DP of 450,000 plants ha(-1) increased the morphological and productive parameters in relation to the other densities studied. The findings of this study indicated that the use of optimal plant densities plays a fundamental role in the growth and productivity of rice, which leads to a sustainable development of the crop.
Keywords: cultivar; sowing densities; Oryza sativa L.; yield